Interobserver Reproducibility Among Gynecologic Pathologists in Diagnosing Heterologous Osteosarcomatous Component in Gynecologic Tract Carcinosarcomas. (July 2017) - Sangoi, Ankur R.; Kshirsagar, Malti; Roma, Andres A.; Horvai, Andrew E.; Chivukula, Mamatha; Ellenson, Lora H.; Fadare, Oluwole; Folkins, Ann K.; Garg, Karuna; Hanley, Krisztina; Longacre, Teri A.; Haas, Jacqueline; et al.
Abstract : Distinguishing hyalinized stroma from osteoid production by a heterologous osteosarcomatous component can be challenging in gynecologic tract carcinosarcomas. As heterologous components in a carcinosarcoma may have prognostic and therapeutic implications, it is important that these are recognized. This study examines interobserver reproducibility among gynecologic pathologists in the diagnosis of osteosarcomatous components, and its correlation with expression of the novel antibody SATB2 (marker of osteoblastic differentiation) in these osteosarcomatous foci. Digital H&E images from 20 gynecologic tract carcinosarcomas were reviewed by 22 gynecologic pathologists with a request to determine the presence or absence of an osteosarcomatous component. The 20 preselected cases included areas of classic heterologous osteosarcoma (malignant cells producing osteoid; n=10) and osteosarcoma mimics (malignant cells with admixed nonosteoid matrix; n=10). Interobserver agreement was evaluated and SATB2 scored on all 20 cases and compared with the original diagnoses. Moderate agreement (Fleiss' κ=0.483) was identified for the 22 raters scoring the 20 cases with a median sensitivity of 7/10 and a median specificity of 9/10 for the diagnosis of osteosarcoma. SATB2 showed 100% sensitivity (10/10) and 60% (6/10) specificity in discriminating classic osteosarcoma from osteosarcoma mimics. Utilizing negative SATB2 as a surrogate marker to exclude osteosarcoma, 73% (16/22) of the reviewers would have downgraded at least 1 case to not contain an osteosarcomatous component (range, 1–6 cases, median 1 case). Gynecologic pathologists demonstrate only a moderate level of agreement in the diagnosis of heterologous osteosarcoma based on morphologic grounds. In such instances, a negative SATB2 staining may assist in increasing accuracy in the diagnosis of an osteosarcomatous component. Abstract : Supplemental Digital Content is available in the text.